Edukasi Pelatihan Transformasi Digitalisasi dalam Mendukung Kewirausahaan Berdampak pada Pendapatan Daerah - Muhammad Tohir; Yuliantini Yuliantini; Aang Gunawan; Basri Fahriza; Olfebri Olfebri (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service initiative aims to promote digitalization to strengthen local entrepreneurship, which in turn contributes to increasing regional revenue. The program focuses on training in using digital technologies, such as social media, online marketplaces, and digital marketing tools, to enhance business effectiveness. Mentoring is provided to help entrepreneurs understand and implement technology-based strategies in their operations. The results show an improvement in participants' digital skills and increased use of technology in business management, leading to higher business income. This growth is expected to contribute to regional revenue through more productive business sectors. Digital transformation has proven to be a strategic approach in fostering innovative and competitive local entrepreneurship.